1997
DOI: 10.1109/34.625116
|View full text |Cite
|
Sign up to set email alerts
|

Shape spectrum based view grouping and matching of 3D free-form objects

Abstract: Abstract-We address the problem of constructing view aspects of 3D free-form objects for efficient matching during recognition. We introduce a novel view representation based on "shape spectrum" features, and propose a general and powerful technique for organizing multiple views of objects of complex shape and geometry into compact and homogeneous clusters. Our view grouping technique obviates the need for surface segmentation and edge detection. Experiments on 6,400 synthetically generated views of 20 free-fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
34
0

Year Published

1998
1998
2003
2003

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 78 publications
(34 citation statements)
references
References 25 publications
0
34
0
Order By: Relevance
“…It stems from the desire to obtain a representative and adequate grouping of views, such that a given level of recognition accuracy may be achieved using the minimum number of stored views [3]. Clearly, this has important implications for the storage space needed to represent each object, and the number of matches which must be performed at run-time for the purpose of recognition.…”
Section: Characteristic Viewsmentioning
confidence: 99%
See 2 more Smart Citations
“…It stems from the desire to obtain a representative and adequate grouping of views, such that a given level of recognition accuracy may be achieved using the minimum number of stored views [3]. Clearly, this has important implications for the storage space needed to represent each object, and the number of matches which must be performed at run-time for the purpose of recognition.…”
Section: Characteristic Viewsmentioning
confidence: 99%
“…However, any other function may be used as the regularization term, and we have investigated several robust measures, including the classical Tukey [5] and Huber [9], and the Adaptive Prior Potential Functions of Li [13]. We also introduced [25] a continuous version of the piecewise Huber robust estimator, described by ´ µ ÐÓ Ó× (3) and found that this yielded the best results by offering a compromise between oversmoothing and noise rejection/numerical stability.…”
Section: Shape From Shadingmentioning
confidence: 99%
See 1 more Smart Citation
“…However, there are two drawbacks to this approach: (1) analytical prediction is impractical in some domains; and (2) synthetic images are not yet realistic enough for general use. More recently, Dorai and Jain [22] have developed a method of view grouping for free from objects, using range images.…”
Section: Related Workmentioning
confidence: 99%
“…A discussion of these techniques falls beyond the scope of this chapter. Interested readers are referred to [12][13][14][15][16][17].…”
Section: The Virtual Boutique: Multimedia Retrieval and Data Mining Fmentioning
confidence: 99%